RELATIONSHIP BETWEEN RISKS MONITORING & CONTROL MANAGEMENT STRATEGY AND SUPPLY CHAIN PERFORMANCE AMONG MANUFACTURING COMPANIES IN KENYA - Kiarie, Dr.David Mburu (International Journal of Supply Chain and Logistics, 2017)
Purpose: The purpose of this study was to determine the relationship between risks monitoring and control management strategy and supply chain performance among manufacturing companies in Kenya. Methodology:The study adopted a cross-section survey of descriptive nature .The target population comprised of the 412 manufacturing companies within Nairobi County that were registered members of KAM. The fisher et al formula for calculating the sample size was used to yield a sample size of199. Data was collected using questionnaires and analyzed using statistical package of social sciences (SPSS) version 21 as a tool of analysis. Results: The study findings revealed that the constructs of risk identification management strategy combined together influenced supply chain performance as supported by a p value of 0.000.Further, most of the companies had risk analysis and evaluation management strategy in place. Policy recommendation:the study recommended that manufacturing companies should put in place a risk analysis and evaluation management strategy to enhance supply chain performance.